Perancangan Aplikasi WMS (Warehouse Management System) untuk Efisiensi Penyimpanan Stock Barang pada Warehouse dengan Metode FIFO (First In First Out) - Rifqi Alif Darmawan Putra; Perani Rosyani (Jurnal Informatika Universitas Pamulang, 2022)
Warehouse is a place for storage of finished goods or semi-finished goods that are collected in one place for the purpose of being used or traded. The main problem in the warehouse is the storage area, sometimes the existing storage is not efficient, causing problems with the accuracy of the stock of goods. The purpose of this research is to make stock storage efficient so that it can increase the accuracy of stock items. The method chosen in this study is FIFO (First in First out) which means that the first goods enter, then the goods are the first to go out, so that the storage of goods in the warehouse becomes more efficient as a result of more regular goods transactions. The results obtained from this study are more efficient stock storage of goods and make goods transactions more orderly. The WMS system that was created still functions to regulate transactions on a basic basis, so that the development of the WMS system to add transaction menus such as reporting and min-max calculations can still be done.